Gratitude buffers the effects of stressful life events and deviant peer affiliation on adolescents’ non-suicidal self-injury - Wei, Chang; Wang, Yu; Ma, Tao; Zou, Qiang; Xu, Qian; Lu, Huixing; Li, Zhiyong; Yu, Chengfu (Frontiers in Psychology, 2022)
Non-suicidal self-injury (NSSI) is an emerging health problem among adolescents. Although stressful life events have been shown to be a key risk factor for adolescent NSSI, the potential mediators and moderators of this relationship are unclear. Based on the social development theory and the organism-environment interaction model, we tested whether the link between stressful life events and adolescent NSSI was explained in part by deviant peer affiliation, and whether this process was buffered by gratitude. A sample of 854 Chinese adolescents (68.50 % female; Mage = 16.35; SD = 1.15) anonymously completed questionnaires to assess the study variables. The results supported the proposed model. The present study demonstrated that stressful life events was linked to adolescent NSSI in part because of deviant peer affiliation, and high gratitude was a key protective factor to buffer this indirect effect. Teaching gratitude may be a helpful component of prevention and intervention programs to reduce adolescent NSSI.